Sequential phosphorus extraction of a 33P-labeled oxisol under contrasting agricultural systems - Buehler, S.; Oberson, Astrid; Rao, Idupulapati M.; Friesen, Dennis K.; Frossard, Emmanuel (2002)
Chemical sequential extraction is widely used to divide soil phosphorus (P) into different inorganic (Pi) and organic (Po) fractions, but the assignment of these fractions to pools of differing plant availability, especially for low P tropical soils, is still matter of discussion. To improve this assignment, the effect of land-use systems and related P fertilizer inputs on size of P fractions and their isotopic exchangeability was investigated. A Colombian Oxisol, sampled from a long-term field experiment with contrasting management treatments, was labeled with carrier free 33P and extracted after incubation times of 4 h, 1, and 2 wk. Phosphorus concentrations and 33P recovery in fractions sequentially extracted with anion exchange resin (Pi), 0.5 M NaHCO3 (Bic-Pi, Bic-Po), 0.1 M NaOH (Pi, Po), hot concentrated HCl (Pi, Po), and residual P were measured for each incubation time. Resin-Pi, Bic-Pi, NaOH-Pi, and hot HCl-Pi were increased with P fertilization, with the highest increase for NaOH-Pi The recovery of 33P in the treatments with annual P fertilization clearly exceeding P outputs indicate that resin-Pi, Bic-Pi, and NaOH-Pi represented most of the exchangeable P. In these treatments, label P transformed with increasing incubation time from the resin to the Bic-Pi and NaOH-Pi fractions. The organic or recalcitrant inorganic fractions contained almost no exchangeable P. In contrast, in soils with low or no P fertilization, more than 14% of the 33P was recovered in NaOH-Po and HCl-Po fractions 2 wk after labeling, showing that organic P dynamics are important when soil Pi reserves are limited.